Bioindicators of heavy metal contamination in soil and vegetation around abandoned mining sites: Implications for ecological restoration - Abbas, Zainab M.; Shandookh, Fatima Kareem (Journal of Degraded and Mining Lands Management, 2026)
Derelict mines are chronic sources of heavy metals, threatening ecosystem integrity and human health. This study evaluated native flora and soil composition as bioindicators of contamination in three abandoned mining areas in Wasit Province, Iraq: Al-Aziziyah (lead-zinc), Old Kut (copper-cobalt), and Northern Al-Numaniyah. Soil and vegetation samples were analyzed via Atomic Absorption Spectrophotometry (AAS) for Pb, Cd, As, Cr, Zn, and Cu. Findings revealed Al-Aziziyah soils exceeded Iraqi/WHO limits for Pb (1,842 mg/kg; 36×) and Cd (12.7 mg/kg; 25×). The Geoaccumulation Index (Igeo) categorized Pb and Cd as "extremely polluted" (Class 6). Atriplex tatarica and Chenopodium murale demonstrated high Bioconcentration Factors (BCF>1) for Pb and Cd, whereas Prosopis farcta exhibited high root-to-shoot translocation (TF>1) for Zn. These indigenous halophytic and ruderal species serve as effective bioindicators and phytoremediation candidates. We propose a bioindicator-based ecological restoration model combining field surveillance, community involvement, and adaptive management to restore disturbed post-mining landscapes in low-resource environments. This solution aligns with Sustainable Development Goals 3 (Good Health) and 15 (Life on Land).